If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -4(x + 6) = 3(8 + -1x) + -1(x + -17) Reorder the terms: 7 + -4(6 + x) = 3(8 + -1x) + -1(x + -17) 7 + (6 * -4 + x * -4) = 3(8 + -1x) + -1(x + -17) 7 + (-24 + -4x) = 3(8 + -1x) + -1(x + -17) Combine like terms: 7 + -24 = -17 -17 + -4x = 3(8 + -1x) + -1(x + -17) -17 + -4x = (8 * 3 + -1x * 3) + -1(x + -17) -17 + -4x = (24 + -3x) + -1(x + -17) Reorder the terms: -17 + -4x = 24 + -3x + -1(-17 + x) -17 + -4x = 24 + -3x + (-17 * -1 + x * -1) -17 + -4x = 24 + -3x + (17 + -1x) Reorder the terms: -17 + -4x = 24 + 17 + -3x + -1x Combine like terms: 24 + 17 = 41 -17 + -4x = 41 + -3x + -1x Combine like terms: -3x + -1x = -4x -17 + -4x = 41 + -4x Add '4x' to each side of the equation. -17 + -4x + 4x = 41 + -4x + 4x Combine like terms: -4x + 4x = 0 -17 + 0 = 41 + -4x + 4x -17 = 41 + -4x + 4x Combine like terms: -4x + 4x = 0 -17 = 41 + 0 -17 = 41 Solving -17 = 41 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(x-4)=x+12 | | 3x^2=8x-3 | | 0.3x^2+0.6x-0.8=0 | | 2160x1/12 | | f(4)=9-6x | | f(0)=9-6x | | f(-4)=9-6x | | 6u^5x-3x^4y^2/3x^2 | | (-10x^2-15x)/(4x^3-9x) | | 0.85x+0.05(10-x)=0.10(-91) | | 10(x-4)+3=8(5-2x)-3 | | 0.70x+0.05(8-x)=0.10(-22) | | 10(4-x)-3=8(5-2x)-3 | | 0.60+0.05(6-x)=0.10(-41) | | x^2-16xy+63y^2= | | 2x+7/21=6-3/7x | | 800x=50896 | | x-5/3=4x+8/6 | | 8*3.14= | | f(x)=2x+x^2+3(4x) | | 16x^2/5x | | 3x-9=48 | | 5/2(-3+2)=3/4+6 | | 7x-18=94 | | x+20=-40 | | [7(n+5)-16]+[3(n-3)+4]= | | x+11=-10 | | (2)3+3y=6 | | 4x^3/(5x^3+5) | | 30+x=69 | | 1.6m=-70 | | 1.6m=-77 |